The sRNA SorY confers resistance during photooxidative stress by affecting a metabolite transporter in Rhodobacter sphaeroides - Adnan, Fazal (RNA Biol, 2015)
Exposure to oxygen and light generates photooxidative stress by the bacteriochlorophyll a mediated formation of singlet oxygen ((1)O(2)) in the facultative photosynthetic bacterium Rhodobacter sphaeroides. We have identified SorY as an sRNA, which is induced under several stress conditions and confers increased resistance against (1)O(2). SorY by direct interaction affects the takP mRNA, encoding a TRAP-T transporter. We present a model in which SorY reduces the metabolite flux into the tricarboxylic acid cycle (TCA cycle) by reducing malate import through TakP. It was previously shown that oxidative stress in bacteria leads to switch from glycolysis to the pentose phosphate pathway and to reduced activity of the TCA cycle. As a consequence the production of the prooxidant NADH is reduced and production of the protective NADPH is enhanced. In R. sphaeroides enzymes for glycolysis, pentose phosphate pathway, Entner–Doudoroff pathway and gluconeogenesis are induced in response to (1)O(2) by the alternative sigma factor RpoHII. The same is true for the sRNA SorY. By limiting malate import SorY thus contributes to the balance of the metabolic fluxes under photooxidative stress conditions. This assigns a so far unknown function to an sRNA in oxidative stress response.